The ability of Arabidopsis to recover from Basta and its application in isolating Cas9-free mutants - Ahmed, Shahbaz; Hulbert, Anna K.; Xin, Xin; Neff, Michael M. (Frontiers in Plant Science, 2024)
After successfully performing Agrobacterium-mediated CRISPR-Cas9-based gene editing in plants, isolation of the Cas9 T-DNA is essential for the stable inheritance of induced mutations. Here, we report a simple technique that allows the isolation of Cas9-free mutants, eliminating the need for outcrossing or other intricate methods such as grafting. This method is based on the ability of Basta-sensitive Arabidopsis thaliana seedlings, which generally perish, to recover and grow once transplanted to Basta-free growth media. By growing gene-edited heterozygous populations of single-locus insertion Basta-resistant plants on Basta selection media, plants lacking the Cas9 T-DNA can be identified. These pale-looking plants lacking Cas9 are then rescued on media lacking the Basta to recover Cas9-free plants. The ability of seedlings to recover from Basta selection was also studied in camelina, canola, and wheat. All three crops showed different recovery rates, with wheat demonstrating the highest recovery once transplanted from Basta to normal growth media. In summary, our findings demonstrate that by harnessing the recovery capability of Basta-sensitive seedlings, we can effectively identify and rescue plants lacking the Cas9 T-DNA, enabling the isolation of Cas9-free mutants in Arabidopsis and potentially extending to other crops.Breeders have contributed to altering animal and plant genomes for years through traditional hybridization and selection to produce new genetic combinations for improved commodity development. This process, however, can take years (Orton, 2020). To overcome this problem, engineered nucleases such as zinc finger nucleases (ZFNs) and transcription activatorlike effector nucleases (TALENs) were discovered to effectively carry out specific genetic changes in plant genomes (Carroll, 2011;Nemudryi et al., 2014). Despite their ability to carry out sitespecific gene editing, engineering through ZFNs and TALENs is time-, effort-, and costconsuming. Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPRassociated nucleases such as Cas9 have emerged recently as breakthrough tools for genome editing studies (Doudna and Charpentier, 2014).First reported in 2011, these molecular scissors are now widely used in labs to make precise cuts in genomic DNA (Zhu et al., 2020). CRISPR was first discovered in the genome